A Tracer Study of Eastern Visayas State University-Ormoc Campus Graduates - Ma. Erenita V. Bahian; Edward B. Bertulfo; Danilo B. Pulma; Robert G. Navarro (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2020)
Tracing graduates offers empirical data about the graduates' employment and competencies. The study aimed to assess relevance of the program's curriculum and seeks to provide empirical data on the employment and competencies of the graduates of Eastern Visayas State University- Ormoc City Campus in 2005-2017 since this is the first time to conduct a tracer study. Using a descriptive survey, 241 graduates responded to a CHED standardized tracer study questionnaire. Frequency counts, percentage, mean, and ranking were used. Results revealed that the most of the graduates who responded were female, single professionals and working in the government with regular or permanent status. Most of the respondents are BS Mechanical and Civil Engineering and mostly Board Examination passers. Some of the respondents landed on their first job within the span of six months with gross monthly salary is within Php 5,000 to Php 15,000. Most of the respondents have stayed with their job for salaries and benefits and have claimed that their job is relevant to the program they took up in the university and they find their learned communication skills to be very useful at work. Graduates should be prepared with the skills and knowledge required to contribute to the success of the licensure examination leading to stable and secure employment. Keywords: tracer study; college students; employment; competencies